Effect of hydrogen addition on the laminar premixed combustion characteristics the main components of natural gas. Issue 4 (August 2019) - Ren, Fei; Chu, Huaqiang; Xiang, Longkai; Han, Weiwei; Gu, Mingyan
Abstract: With the increasing use of natural gas, improving the thermal efficiency and reducing emissions has become the major goals in its combustion. The objective of the present work is to investigate the effect of hydrogen addition on the combustion characteristics of natural gas. A ChemkinⅡ/Premix Code with the detailed chemical reaction mechanisms was employed with the Soret effect taken into account in all the calculations. With the mole fraction of hydrogen in the fuel varied from 0 to 40% at different initial temperatures (298–500 K) and pressures (1–8 atm), the results showed that the laminar burning velocities (LBVs) and the adiabatic flame temperatures of the C1 C4 four alkanes increased with increasing hydrogen-doping ratio. The LBV and the adiabatic flame temperature of methane displayed the maximum increase with the hydrogen-doping ratio. Additionally, the generation of active radicals H, O, and OH during the combustion process was strongly correlated with the LBV. The sensitivity of the flame temperature in four alkane fuels present in the natural gas at the maximum temperature gradient was analyzed. At a constant hydrogen-doping ratio, the LBV and the adiabatic flame temperature increased significantly with the increasing initial temperature. With increasing the pressure, the LBV gradually decreased while the adiabatic flame temperature increased. Highlights: The LBV and temperature of tested fuels increase with increasing the hydrogen-doping ratio. The active radicals H, O and OH are strongly correlated with the LBV. The most important promoting reactions on the rise of flame temperature are H + O2 = O + OH and OH + CO =CO2 + H. With the increase of the pressure, LBVs are reduced to about 1/3 of the original values. LBVs could be increased up to 2.5 times as the initial temperature varied from 298 K to 500 K.